International Dental Aid and WWII - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2014)
During the liberation of the camps, a great majority of the detainees died after eating abundantly within a short period of time. A thousand men died because the Americans and the Englishmen were totally bewildered and overwhelmed with what was in front of them. In good faith, they gave a great amount of food to the survivors without thinking of the dramatic consequences that this was going to cause. Indeed, the survivors' weakened bodies could not bear too much food. As a result, they changed their minds and they set up field hospitals which were to feed the sick through successive steps. Doctor Samuel Glashow [1] was the chief dental officer of the 307th medical company of the 82nd American Aeronautical Division in 1945. On March and April of that same year, he took part in the liberation of the Ludwiglust concentration camp in the North of Germany. Here is what he remembered. I have been with the 82nd Division since 1942 and we conducted seven combat missions. Two months before the end of the war, we were occupying Ludwiglust where the German army had been before. My superior and a dental officer, Major Works and I decided to go and see the infamous concentration camp. What we saw was beyond unimaginable.